Analsis Kelayakan Usahatani Durian Duri Hitam Selama Satu Periode Produksi di Watu Mori Farm, Kecamatan Mbeliling Kabupaten Manggarai Barat - Samur, Eldis Suasana; Payong, Polikarpus Payong; Piran, Ronaldus Don (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This research aims to analyze the feasibility of black durian farming during one production period at Watu Mori Farm, Mbeliling District, West Manggarai Regency. This research was carried out from December 2023 to February 2024. The research method used was descriptive, data collection techniques used interviews, documentation, observation, and participation. Data information was obtained directly from the Watu Mori Farm manager. The data analysis techniques used are cost analysis, revenue analysis, income analysis, and farming feasibility analysis. The results of this research show that the total costs were Rp 66,825,240, and the income obtained during black thorn durian farming during one production period was Rp 113,250,000, with a total net income of Rp. 46,424,760. Based on the research results, it show that blackthorn durian farming during one production period at Watu Mori Farm is said to be worthy of development. It is said to be worthy of development because the B/C ratio is greater than 1, namely 1.69. The problems faced during the blackthorn durian farming process at Watu Mori Farm are pests and diseases that attack the plants, especially during the season.